Effect of parathyroidectomy on epicardial fat thickness as a cardiovascular risk factor in patients with primary hyperparathyroidism - KIZILGÜL, Muhammed (Turk J Med Sci, 2019)
BACKGROUND/AIM: Several studies demonstrated that primary hyperparathyroidism is related to increased risk for cardiovascular diseases (CVDs), and risk is decreased by parathyroidectomy. Epicardial fat thickness (EFT) has been postulated as a new marker of CVD risk. We evaluated the impact of parathyroidectomy on EFT in patients with primary hyperparathyroidism (PHPT). MATERIALS AND METHODS: Thirty-four PHPT patients (29 female, 5 male) and 28 age- and sex-matched controls (19 female, 9 male) were included in the study. Demographic, anthropometric, and biochemical data were recorded both before parathyroidectomy and 6 months after the procedure. Epicardial fat thickness was measured by transthoracic echocardiography. RESULTS: Mean age was 53.15 ± 8.44 years. Mean preoperative EFT was higher than mean EFT in the control group (0.49 ± 0.07 cm to 0.46 ± 0.08 cm, P: 0.0005), and EFT decreased after parathyroidectomy (0.49 ± 0.07 cm to 0.44 ± 0.08 cm, P: 0.0005). Systolic blood pressure and calcium, parathormone, and hsCRP levels decreased after parathyroidectomy (P < 0.05). Vitamin D levels increased (P < 0.05). Diastolic blood pressure, body mass index, carotid intima-media thickness, and HOMA-IR, fasting plasma glucose, and phosphorus levels were unchanged after parathyroidectomy (P > 0.05). Preoperatively, EFT was correlated with SBP (r: 0.360, P: 0.0285) and age (r: 0.466, P: 0.0036). Multiple linear regression used to identify independent predictors of change in epicardial fat did not find any predictor of change in epicardial fat (P > 0.05). CONCLUSION: EFT was decreased by parathyroidectomy in patients with primary hyperparathyroidism.However, the decrease in EFT was not correlated with any of the cardiovascular risk factors. More comprehensive studies evaluating the potential relation between PHPT and EFT need to be conducted.